Does a "moderate" alcohol intake damage the brain?. Issue 7 (July 1988) - Harper, C; Kril, J; Daly, J
Abstract : A range of volumetric and neurochemical analyses were carried out on the brains of 14 "moderate" drinkers. These data were compared with previous studies from controls and alcoholics. Volumetric measurements consistently suggest a loss of cerebral tissue although the differences were not statistically significant. Changes in the lipid and water content of the white matter were noted and the significance of these changes in relation to the pathogenesis of reversible brain shrinkage caused by alcohol abuse is discussed.